EDUKASI PEMAHAMAN BENTUK SEDIAAN FARMASI MELALUI APOTEKER CILIK DI SDN 3 PANARUKAN, TABANAN, BALI - Sawiji, Repining Tiyas; Sukarya, Dewa Ayu Kade Devina Krisyanti Dewi; Wikayanti, Ni Putu Ayu Putri (Universitas Sanata Dharma, 2025)
The public's lack of understanding of drug dosage forms can lead to errors in drug use. These medication errors can affect the success of therapy. Therefore, education on the knowledge of pharmaceutical dosage forms through Apoteker Cilik program can be implemented so that children take an active role in conveying drug-related information to the surrounding environment from an early age. This activity aimed to increase knowledge about the role of pharmacists and drug dosage forms in the community. The method used in this activity is an interactive presentation through PowerPoint media, games, and evaluation (pretest and posttest). The evaluation results of this community service activity showed an increase in knowledge, as seen from the average pretest and posttest scores. The pretest score was 66.79%, while the posttest score was 78.57%. The evaluation data were also analyzed using the Wilcoxon signed-rank test. The results showed a significant difference in the participants' knowledge before and after the provision of the material. The test produced a significance value of 0.000 (p 0.05). Based on the results, it can be concluded that this community service activity ran well and made a significant positive difference.